PENGARUH CITRA MEREK DAN BRAND AMBASSADOR TERHADAP KEPUTUSAN PEMBELIAN DI LAZADA MELALUI KEPERCAYAAN KONSUMEN - Andari, Titiek Tjahja; Irfansyah, A; Gunawan, Rachmat (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.09.TAHUN.2024DO - 10.24843/EEB.2024.v13.i09.p05, 2024)
Competing in online marketing forces companies to have a good brand image to influence purchasing decisions. This study aimed to determine how brand image and brand ambassadors influence consumer purchasing decisions on the Lazada e-commerce platform through consumer trust. The sample consisted of 384 out of 4,445 Djuanda University students, selected based on being Lazada consumers with at least two transactions. The sampling method used was proportionate stratified random sampling. Quantitative methods were employed using questionnaire instruments and analyzed through Path Analysis, t-statistics, and the Sobel test with SPSS software. The results showed that the brand image variable has a positive and significant direct effect on consumer trust, as does the brand ambassador variable. Brand image have positive and significant effects on purchasing decisions, brand ambassador also have positive and significant effects on purchasing decisions, while consumer trust also has a positive and significant effect on purchasing decisions. Additionally, consumer trust was found to mediate the relationship between brand image and brand ambassadors on purchasing decisions.